Psychological components of professional communication problems in the situation of reporting a diagnosis and adverse news - Mukharovska Інна; Asanova Азізе (Psychosomatic Medicine and General Practice, 2024)
Establishing and delivering diagnosis in medical practice is a common and mandatory component of a doctor’s professional activity. Along with this, a number of diagnoses characterized by an unfavorable prognosis for life can cause significant changes in the patient’s mental health, so informing the patient can become a difficult task. A qualitative analysis of doctor-patient communication about life-threatening diseases was carried out and the main psychological problems that arise during such communication were determined. The main negative expectations of doctors in the situation delivering bad news are: intense negative emotions in patient; the possibility development of mental disorders in the patient; projecting negative emotions on the doctor who reported the news; complication of further communication with the patient in connection with the growth of mental distress; discomfort when answering "uncomfortable questions"; responsibility imbalance. Improving the professional communication of doctors can be provided by increasing knowledge in clinical psychology, communication skills. But also important is psychological state and dynamics of the doctor’s own experiences during reporting a diagnosis, self-observation, reflection and psychological self-help skills, are also an important component. Key words: doctors, medical communication, communicative competence, delivering bad news, SPIKES, professional stress, oncology, psycho-oncology, cancer patients.